Issues and Approaches to Gifted Education in Specialist Music Programs Globally : Insights From Institutional Leaders - López-Íñiguez, Guadalupe; McPherson, Gary E. (Sage, 2025)
Globally, a range of specialized talent development music programs offer training for young musically gifted children to develop their musical abilities to an advanced, professional level of performance. In recent years, various constituencies have reported on significant shortcomings in some of these programs, sparking intense debates concerning the necessity of continuing what they view as overly specialized talent development programs. Presently, there has been no comprehensive and systematic overview of the current situation for gifted children in specialist music education. This qualitative, collective case study examines the current challenges identified by 81 leaders overseeing 68 specialized music programs in 25 countries. Findings reveal a wide array of critical issues and approaches to specialized music education for gifted children that range from a focus on serving the children to a focus on children serving the system. The study emphasizes how diverse stakeholders can recognize gifted children as individuals, and not just as potential musicians who benefit others.
Keywords: lahjakkuus; musiikkioppilaitokset; musiikkikasvatus; lapset (ikäryhmät)